PENGARUH FRAUD TRIANGLE DAN PROFITABILITAS TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN GCG SEBAGAI VARIABEL MODERATING - Carry Setiawan; Herlin Tundjung (Jurnal Kontemporer Akuntansi, 2023)
Fraudulent financial reporting is the deliberate neglect of amounts and disclosures with the intention of deceiving users of financial statements. This fraud usually occurs when a company reports higher than it actually (overstates) its assets or revenues, or when a company understates its liabilities and expenses. This research was conducted to determine the effect of pressure, opportunity, rationalization and rofitability on Fraudulent Financial Reporting with good corporate governance as a moderating variable. The method used in this research is quantitative research methods using panel data regression processing techniques with the help of the EVIEWS 9.0 program. The results showed that Pressure and opportunity had a positive and significant effect on fraudulent financial reporting. Meanwhile, GCG moderates the effect of pressure and opportunity on fraudulent financial reporting.